Thomas Dallery, Le divorce rentabilité/croissance dans le capitalisme financiarisé. Changements de régimes, équilibres, instabilités et conflits - Thomas Dallery (Revue de la Régulation)
The divorce between profitability and growth that emerged since the 80s raises a paradox that has to be explained. The macroeconomic realisation of profits being determined by capitalists’ spendings, the slowdown of accumulation cannot come (theoretically) with a profitability recovery, others things being equal.After having recalled, in a first chapter, that financialisation is only the last avatar of a long trend for capitalism to escape from real economy, we show, in a second chapter, that financialisation leads, for the individual firm, to a reorientation towards shareholders’ profitability claims at the expense of managers and capital accumulation, financial (indebtedness) and real (capacity utilisation) security, and also of workers (real wage).After having faced, in a third chapter, two methodological, embarrassing questions for kaleckian models of growth and distribution (not very plausible and unstable for the most plausible ones), we use, in a fourth chapter, a second macroeconomic approach (stock-flow consistent model) where conflict impacts distribution (conflict inflation) and accumulation (growth/profit trade-off). We show that dividends distribution and share buybacks allow, within the limits permitted by indebtedness, for a stimulation of rentiers’ consumption and for the realisation of profitability claims, in spite of the slowdown of accumulation.